Financial incentive schemes in a TQM environment : a case study in a world class organisation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Industrial and Manufacturing Technology at Massey University - Soliman, Wassim (Massey University, 2000)
Whether or not financial incentive schemes help organisations to reach their objectives is an old debate. During the last few decades, the modern management schools -Total Quality Management (TQM) and new manufacturing techniques-added extra pressure on financial incentive schemes by claiming that such schemes don't fit in a modern management environment and that they can have a destructive influence on organisations. Although the advocates of TQM and modern manufacturing management techniques have different views concerning financial incentive schemes, generally speaking, they don't believe that these schemes help modern organisations to reach their objectives. Some of these advocates see that financial incentive schemes motivate employees to focus on quantity and ignore quality. Others see that although those schemes can help to achieve progress, that progress is at the expense of the intrinsic rewards that organisations should promote. Other TQM advocates believe that these schemes do not help because effective and efficient systems rather than individuals are the main factor that determines the progress of organisations. This category believes that it makes more sense to improve the systems and procedures rather than to use financial incentive schemes to motivate employees to reach the organisations' targets. The purpose of this research project was to answer the question as to whether a compromise between TQM and financial incentive schemes could be achieved to make the best use of both approaches. To answer this question an organisation with a strong TQM environment was identified and a financial incentive scheme was designed and implemented in that organisation with the help of a design team from the same organisation. The scheme covered five main areas of interest to the organisation namely: product and process quality, manufacturing management, environmental compliance, safety compliance and cost effectiveness. From several key performance indicators (KPIs) used by the organisation in these five areas only those under the direct control of employees were used in this research project. Samples of employees from the departments covered by the incentive scheme were consulted all through the different stages of the development of the incentive scheme. A comprehensive communication plan was undertaken to ensure that the structure and principles of the incentive scheme were clearly communicated to all employees. The results of installing the financial incentive scheme were then analysed to study the effect of implementing that scheme on the organisational performance and on the TQM environment and particularly on some specific TQM attributes. The analysis of those results showed that the incentive scheme achieved a considerable improvement in almost all of the areas covered by the scheme. The analysis showed no evidence of any adverse effect on the TQM environment as a result of installing the incentive scheme. In fact it was concluded that the TQM environment assisted the implementation of the financial incentive scheme.
Keywords: Manufacturing industries; Case studies; Incentives in industry